PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT SUKU MELAYU DI DESA SUNGAI DAUN KECAMATAN SELAKAU KABUPATEN SAMBAS - Meisia, Lili; Rafdinal, Rafdinal; Ifadatin, Siti (Universitas Tanjungpura, 2020)
The Malay Tribe in West Kalimantan are the largest after Dayak Tribe. The most people in Sungai Daun Village are Malay Tribe who still use plants as medicine. This research was conducted with the aim to know the types of medicinal plants, parts of plants used as medicines and methods of processing and the use of plants as medicine. The research was conducted in Sungai Daun Village, Selakau Sub-District, Sambas District. The research method using snowball sampling with 12 respondents consist of village heads, herbalist, shaman giving birth and other community members who have knowledge about medicinal plants. The results showed that there were 74 species of plants included in the 43 families used as medicine. The highest percentage of families is Asteraceae (6,8%), Euphorbiaceae (6,8%) andPiperaceae (6,8%). Part of a widely used plant as medicine is the leaves (48,8%), while the way of processing and the use of medicinal plants is in boiled (55,3%) and drunk (48,3%).